PHENOTYPICAL VARIABILITY OF WILD POPULATIONS AND CULTURE STOCK OF RAINBOW TROUT ONCORHYNHUS MYKISS IN WATER BODIES OF THE BALKHASH BASIN (Experimental biology, 2023)
The rainbow trout, or mykiss Oncorhynchus mykiss, is one of the most important aquaculture and introduced species worldwide. For the rational use and management of salmon stocks, various methods are used, of which phenetic analysis is one of the simplest, but effective. The authors analyzed the variability of color (spots) in trout populations from 1) Lake Kolsay, which originated from a cultural form from farms in Europe; 2) from the Kopak River, which originated from the wild populations of Kamchatka; 3) farmed trout of Danish and Polish origin. Data on the frequency of occurrence of various phenes and the proportion of rare morphs are given, and the index of similarity of populations is calculated. The dendrograms were constructed based on the similarity score using the complete linkage and unweighted pair-group similarity (UPGMA) methods. Significant differences between the trout from the Kokpak River and all other studied forms and the absence of variability in the stock of trout of Polish origin were revealed. The data obtained can be used to identify the sources of rainbow trout entering new water bodies and assess the risk for native ichthyofauna, as well as provide a preliminary assessment of the existing genotypic diversity of this alien species.
Keywords: rainbow trout; Oncorhynchus mykiss; Balkhash basin; phenotype; variability